Predicting students’ communication in online learning social networks - Zaphiris, Panayiotis; Laghos, Andrew (My University, 2012)
This paper provides a new approach for analysing social networks that are formed around e-Learning environments. A combination of three methods (Social Network Analysis, Collectivist Online Learning Environment Survey, Attitudes Towards Thinking and Learning Survey) was applied to a case study of an online course. Following this, correlations were carried out between the students’ responses to the questionnaires and their actual social interaction in the elearning course. Based on these results we were able to provide insights on methods that can be used to predict the students’ social interactions when they take part in communication activities in e-Learning environments.
Keywords: Computer-mediated communication; Human-computer interaction; Social networks; Internet